X-inactivation normalizes O-GlcNAc transferase levels and generates an O-GlcNAc-depleted Barr body - Olivier-Van Stichelen, Stéphanie; Hanover, John A. (Frontiers in Genetics, 2014)
O-GlcNAc Transferase (OGT) catalyzes protein O-GlcNAcylation, an abundant and dynamic nuclear and cytosolic modification linked to epigenetic regulation of gene expression. The steady-state levels of O-GlcNAc are influenced by extracellular glucose concentrations suggesting that O-GlcNAcylation may serve as a metabolic sensor. Intriguingly, human OGT is located on the X-chromosome (Xq13) close to the X-inactivation center (XIC), suggesting that OGT levels may be controlled by dosage compensation. In human female cells, dosage compensation is accomplished by X-inactivation. Long noncoding RNAs and polycomb repression act together to produce an inactive X chromosome, or Barr body. Given that OGT has an established role in polycomb repression, it is uniquely poised to auto-regulate its own expression through X-inactivation. In this study, we examined OGT expression in male, female and triple-X female human fibroblasts, which differ in the number of inactive X chromosomes (Xi). We demonstrate that OGT is subjected to random X-inactivation in normal female and triple X cells to regulate OGT RNA levels. In addition, we used Chromosome isolation by RNA purification (ChIRP) and immunolocalization to examine O-GlcNAc levels in the Xi/Barr body. Despite the established role of O-GlcNAc in polycomb repression, OGT and target proteins bearing O-GlcNAc are largely depleted from the highly condensed Barr body. Thus, while O-GlcNAc is abundantly present elsewhere in the nucleus, its absence from the Barr body suggests that the transcriptional quiescence of the Xi does not require OGT or O-GlcNAc.